2014
DOI: 10.1071/wf12152
|View full text |Cite
|
Sign up to set email alerts
|

Verification of WRF modelled fire weather in the 2009–10 New Zealand fire season

Abstract: Abstract. The Weather Research and Forecasting (WRF) mesoscale model was used to simulate the fire weather conditions for the 2009-10 wildland fire season in New Zealand. The suitability of WRF to simulate the high-end fire weather conditions for this period was assessed through direct comparison with observational data taken from 23 surface and two upper-air stations located across New Zealand. The weather variables and fire weather indices considered in the verification were the 1200 hours NZST air temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…While the performances of various air-quality models in predicting anthropogenic and wildfire-caused aerosol distributions have been evaluated by means of data from surface and aircraft measurements [4], such evaluations are nonexistant for Interior Alaska. Here, the lack of data from aircraft field campaigns and the sparse availability of air-quality surface observations has limited the assessment of model performance.…”
Section: Introductionmentioning
confidence: 99%
“…While the performances of various air-quality models in predicting anthropogenic and wildfire-caused aerosol distributions have been evaluated by means of data from surface and aircraft measurements [4], such evaluations are nonexistant for Interior Alaska. Here, the lack of data from aircraft field campaigns and the sparse availability of air-quality surface observations has limited the assessment of model performance.…”
Section: Introductionmentioning
confidence: 99%
“…Regional downscaling serves to capture local terrainintroduced effects such as pollution channeling through valleys, accumulation under inversions, or redistribution by mesoscale circulations. Various studies showed WRF's capability to predict mesoscale features when driven with analysis data [19] [61]. Therefore, we compared monthly mean diurnal course of 2m temperature, 2m relative humidity, 10m wind speed, and wind direction over the entire domain, over land, ocean, coastal areas, and Glacier Bay obtained by EXP with those of CON to assess whether the climatologies from downscaling provide similar magnitudes in response to these regional/local features.…”
Section: Discussionmentioning
confidence: 99%
“…CESM used a mosaic approach for the various plant-functional types [75]. Any mosaic approach simplifies and smoothens the heterogeneity of the landscape [61] [76], for which the likelihood for overestimation of wind speed increases.…”
Section: Windmentioning
confidence: 99%
“…Physics-based mesoscale atmospheric numerical models are tools that can be used to provide a good understanding of the finescale variability of weather and climate across a vineyard area, even in regions of complex terrain (Bonnardot and Cautenet, 2009;Soltanzadeh et al, 2016). These models have been used to address a range of other applied problems, including dust and air pollution dispersion, wild fire behaviour and wind energy resource assessment (Purcell and Gilbert, 2015 ;Alizadeh Choobari et al, 2012;Simpson et al, 2013;Sturman et al, 2011;Titov et al, 2007).…”
Section: Introductionmentioning
confidence: 99%